A Case of Transcatheter Aortic Valve Implantation in a Centenarian Patient. (18th November 2021) - Badr, Salem; Johnsrud, Daniel O.; Sherry, Charnai D.; Allaqaband, Suhail Q.; Weiss, Eric S.; Bajwa, Tanvir K.
Abstract : Calcified aortic stenosis has become the most common form of acquired valvular heart disease in very old patients. Despite this fact, a majority of these patients were turned down by surgery owing to a risk of mortality > 10 % in patients older than 90 years. In recent years, transcatheter aortic valve implantation (TAVI) has emerged as a therapeutic option for severe aortic stenosis. However, there is a paucity of data regarding the outcomes of TAVI in patients older than 100 years. We present the oldest patient who has undergone successful TAVI reported in the current literature.